1986
DOI: 10.1128/mcb.6.10.3428
|View full text |Cite
|
Sign up to set email alerts
|

Repair-deficient xeroderma pigmentosum cells made UV light resistant by fusion with X-ray-inactivated Chinese hamster cells.

Abstract: Xeroderma pigmentosum (XP) is an inherited human disease caused by a malfunction in the dimer excision step of DNA repair. The disease is manifested as an extreme sensitivity to UV light resulting in the development of skin cancers and, in some cases, neurological disorders. At least nine complementation groups have been identified, indicating that the disease comprises a variety of mutations at several genetic loci (2, 5). The genetic basis of the physiological defect of XP has not yet been characterized. Nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
1

Year Published

1987
1987
2004
2004

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
0
8
1
Order By: Relevance
“…Our results differ from those observed in cell fusion experiments in which heterokaryons formed from eukaryotic cells displaying widely diverse repair capacities (14–16) showed enhanced repair relative to the parental cells. Studies by Paterson and Lohman (14) showed that two distinct repair systems ( i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results differ from those observed in cell fusion experiments in which heterokaryons formed from eukaryotic cells displaying widely diverse repair capacities (14–16) showed enhanced repair relative to the parental cells. Studies by Paterson and Lohman (14) showed that two distinct repair systems ( i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…This is due, at least in part, to the reduced amounts of stably integrated DNA in human lines relative to many rodent lines (14,47). Some success with correction of XP cells has been achieved by fusion of X-ray-inactivated CHO cells with XP group A (17), resulting in primary hybrids having -2% hamster DNA. Thus far, cell fusion studies between CHO UV mutants and XP cells have failed to identify any overlap in these complementation groups (40).…”
mentioning
confidence: 99%
“…The sensitivity of XP cells in culture to UV light (254 nm) is 5-to 10-fold greater than nQrmal (1,15), and the cells fail to repair a wide range of radiation-and chemically induced DNA damage (5, 10, 27), including (5-5,6-6)cyclobutane pyrimidine dimers and (6-4) pyrimidine-pyrimidone photoproducts, measured by radioimmunoassay (4, 19-21) and enzymatic methods (7,13,14,44). The relative proportions of cyclobutane dimers to other photoproducts determined from their photoreactivation suggest that (6-4) photoproducts may account for as much as 30% of the total lesions (24), and they are highly mutagenic (2).…”
mentioning
confidence: 99%
“…1C), a response characteristic of the mex phenotype of XP12RO (8,31). Normal, XP12RO, and XP129 cells all had similar sensitivity to mitomycin C, with a D37 concentration of 45 nM (Cleaver and Thomas, in press), consistent with the results of Fujiwara et al (11) with normal and XP cells.Cyclobutane pyrimidine dimers in DNA were quantified in purified DNA by digestion with Micrococcus luteus UV endonuclease, as previously described (7,13,14). On the basis of this assay, the XP129 revertant and the parental XP12RO cell line both appear to be defective in the removal of cyclobutane dimers (Table 1), whereas the two normal cell lines removed about 60% of the initial number of dimers in 24 h. When repair of cyclobutane and (6-4)pyrimidinepyrimidone dimers was monitored by radioimmunoassays that specifically detect these lesions in DNA (18,20,21,36), slightly different results were obtained.…”
mentioning
confidence: 99%